Cyclin-dependent kinase 5/Collapsin response mediator protein 2 pathway may mediate sevoflurane-induced dendritic development abnormalities in rat cortical neurons. (9th June 2017) - Liu, Yafang; Lin, Daowei; Liu, Chuiliang; Zhao, Yifan; Shen, Zhiwen; Zhang, Kun; Cao, Minghui; Li, Yujuan
Highlights: Sevoflurane led to CDK5 activation by increasing p25 expression. Sevoflurane increased the expression and cytoplasmic distribution of phospho-CRMP2 (Ser522). Sevoflurane suppressed dendritic branching by activating the CDK5/CRMP2 pathway. Abstract: Sevoflurane has been reported to induce neurotoxicity and cognitive impairment in the developing brains. However, the underlying molecular mechanisms remain poorly understood. Recent studies have demonstrated aberrant cyclin-dependent kinase 5 (CDK5) activity is implicated in inhaled anesthetic-induced neurotoxicity. CDK5/CRMP2 signaling is involved in the cortical and hippocampal dendritic development. The aim of present study is to investigate whether the CDK5/CRMP2 pathway mediates sevoflurane-induced dendritic development abnormalities. Rat primary cortical neurons were treated with 4% sevoflurane for 6 h, the CDK5 inhibitor roscovitine or the vehicle (0.3% DMSO) was administered 12 h before sevoflurane or carrying gases exposure. Cortical neurons were harvested for further analysis 0 h, 12 h and 24 h after exposure. Sevoflurane exposure for 6 h did not reduce cell viability and slightly increased the expression of cleaved caspase-3. Sevoflurane induced abnormal CDK5 activation by increasing the expression of its activator p25 and promoted the phosphorylation of CRMP2 (Ser522). The increased phospho-CRMP2 (Ser522) was mainly distributed in the cytoplasm of cortical neurons. Sevoflurane significantly reduced the number of primary dendrites and the number of branching points; whereas it did not influence the total dendritic length. Suppression of CDK5 activation with roscovitine attenuated neuronal apoptosis, hyperphosphorylation of CRMP2 (Ser522) and dendritic development abnormalities induced by sevoflurane. Our results indicate that activation of the CDK5/CRMP2 pathway may mediate sevoflurane-induced dendritic development abnormalities in the cortical neurons. The physiological significance of these findings remains to be determined.